Quantification of the Surface Coverage of Gold Nanoparticles with Mercaptosulfonates Using Isothermal Titration Calorimetry (ITC) - Tomaszewska, Emilia; Stępniak, Artur; Wróbel, Dominika; Bednarczyk, Katarzyna; Maly, Jan; Krzyżowska, Małgorzata; Celichowski, Grzegorz; Grobelny, Jarosław; Ranoszek-Soliwoda, Katarzyna (The journal of physical chemistry. B, 2024)
This manuscript presents a comprehensive study on the quantification of modifier molecules adsorbed on gold nanoparticles (AuNPs) using two complementary techniques Ellman's method (UV-vis spectroscopy) and isothermal titration calorimetry (ITC). In this paper, we compare the feasibility of using the ITC technique and Ellman's method to study the interactions of mercaptosulfonate compounds (sodium mercaptoethanesulfonate, MES, and sodium mercaptoundecanesulfonate, MUS) with the surface of AuNPs of various sizes. The thermodynamic functions of the attachment of mercaptosulfonates to AuNPs were determined, revealing a linear relationship between the number of adsorbed molecules and the surface area of the nanoparticles. The amount of MES and MUS determined by Ellman's method (7 and 11 molecules per square nm, respectively) is more than twice that measured by the ITC technique (3 and 4 molecules per square nm, respectively). The slight differences in the adsorption of MES and MUS on the gold surface are due to differences in the carbon chain length of the ligand molecules. In the case of MES, the formation of the Au-S bond is the dominant stage of the adsorption process, whereas for MUS, the ordering process and self-assembly of molecules on the gold surface are dominant.